Electrochemical Aptasensors for Biological and Chemical Analyte Detection. Issue 2 (20th October 2020) - Nur Topkaya, Seda; Cetin, Arif E.
Abstract: Aptamers are short length, single‐stranded DNA or RNA affinity molecules which interact with any desired targets such as biomarkers, cells, biological molecules, drugs or chemicals with high sensitivity. They have been extensively employed for medical applications due to having more advantages than the antibodies such as easier preparation and modification, higher stability, lower batch‐to‐batch variability and cost. Moreover, aptamers can be easily integrated efficiently with sensors, biosensors, actuators and other devices. In this review article, different applications of aptamers for biological and chemical molecules detection within the scope of electrochemical methods were presented with recent studies. In addition, the present status and future perspectives for highly‐effective aptasensors for specific and selective analyte detection were discussed. As in stated throughout the review, combining of extraordinary properties of aptamers with the electrochemical‐based biosensors could have improved the sensitivity of the assay and reduced limit of detection. Abstract :